Transformasi Industri Hulu Migas Menuju Energi Bersih: Studi Literatur Tantangan dan Strategi Implementasi Carbon Capture and Storage di Indonesia - Farsya Fatihatul Nizma Tatuhey; Havidh Pramadika; Mulia Ginting; Lisa Samura (Universitas Proklamasi 45, 2025)
The upstream oil and gas industry is under global pressure to reduce carbon emissions while maintaining production levels. One of the key technologies projected to play a vital role in this energy transition is Carbon Capture and Storage (CCS). This technology captures carbon dioxide (CO₂) emissions from industrial activities and stores them in underground geological formations, including depleted oil and gas reservoirs. Indonesia, as an oil-producing G20 member, has a significant opportunity to develop CCS due to the availability of geological formations suitable for carbon storage. This study aims to identify the potential, challenges, and implementation strategies of CCS in Indonesia’s upstream oil and gas sector through a literature review and conceptual analysis approach. The findings indicate that CCS implementation could support Indonesia’s Net Zero Emission 2060 target, although challenges remain in terms of financing, regulatory framework, and technological readiness. Strategic efforts such as policy strengthening, cross-sector collaboration, and human capital development are essential to accelerate CCS deployment.